First MBBS: three decades ago - Shankar, P Ravi (Research and Humanities in Medical Education, 2022)
For several decades the first MBBS (undergraduate medical course) in India was of 18 months duration. This time was exclusively devoted to learning the preclinical subjects of Anatomy, Physiology, and Biochemistry. There was little to no early clinical exposure and communication skills, empathy, the patient perspective, and the medical humanities were not addressed. In this article, the author discusses his preclinical years in a government medical college in Kerala, India.